Crystal Structure and Physico-Chemical Properties of Diaquabis(1,10-Phenanthroline)manganese(II) Disaccharinate Monohydrate - Yilmaz, V.T.; Yilmaz, F.; Topcu, Y.; Andaç, O.; Göven, K. (Elsevier Science BV, 2001)
A novel manganese complex, [Mn(phen)2(H2O)2](sac)2· H2O, was synthesized by the reaction of [Mn(sac)2(H2O)4]·2H2O with 1,10-phenantroline in aqueous solution and characterized by elemental analysis, IR spectral evidence, magnetic measurements, thermal analysis and single crystal X-ray diffraction. The compound crystallizes in triclinic system, space group P-1, with Z = 2. The saccharinate ions do not coordinate the central metal, instead are present as the complementary anions. In the complex cation, Mn(II) is coordinated by two phen and two aqua ligands, and exhibits a distorted octahedral coordination with a high-spin configuration. The presence of lattice and coordinate water molecules are also confirmed by thermal analysis and IR spectroscopy. © 2001 Elsevier Science B.V.
Keywords: 1,10-Phenantroline Complexes; Crystal Structure; Mn(II) Complexes; Saccharinates; Spectra; Thermal Analysis